(3YHbQjI GdUOjb (B/s - (3GdYbGO, eMehO s ((3GdbGgQI (B:s (3OGQ GdeYGQa ,s, 2012)
(3YHbQjI GdUOjb gh GMO cJH SdSdI YHbQjGJ GdUOjb GdJj JfGhd GdMOjK Yf QShd Gddg h CUMGHg h dcfgG djSJ HcJmH ddSjQI ceG JYhOfG YdjgG h dG JgOa Gdi JCQjN GMOGK h dG PcQ SjQI TNUjI h GfeG GJLg ajgG GdYbGO Gdi fHT GSQGQ TNUjGJ h JMdjdgG HCSdhHg GdYHbQj ef NdGd JYGedGJgG h eG Qhj YfgG ef GUMGH GdeYfj h eG JfGbdg ef YGjThGg(B. (3JLO aj gPG GdcJGH GehQ cKjQI dG fSeYgG Yf gPG GdGfSGf (B" (3KGfj GKfjf (B" (3Ghd ebJO h Ghd NdjaI HYO QShd Gddg h gh aj fXQjI TNUjI de JDJ MbgG HYO aj GdMOjK YfgG Ydi GdQZe eeG cGf dh ef OhQ aj HfGA GdOhdI GdGSdGejI h GdMaGX YdjgG HYO QShd Gddg h gh ceG jbhd GdEeGe Ydj QVj Gddg Yfg aj JCHjf GdUqOjb (B: " (3cfJ cGdLHd GdPj dG JMQcg GdYhGUa hdG JRjdg GdbhGUa (B.. (3cfJ ceG bGd QShd Gddg Udi Gddg Ydjg hSde VYjakG aj HOfc bhqjkG aj CeQ Gddg , eJhGVYkG aj faSc YXjekG YfO Gddg , LdjdG aj GdCQV cHjQkG YfO GdeDefjf , hde jcf dCMO YfOc eWeY , hdG dCMO YfOc ghGOI , aGdbhj YfOc VYja MJi JCNP GdMb efg , hGdVYja YfOc bhj MJi JCNP GdMb dg (B.. (3adG MQefG Gddg CLQc , hdG CVdfG HYOc (B.. " (3TNUjI SJMHgG GcKQ HYO gPG GdcJGH TNUjI bGd ajgG YeQ Hf GdNWGH QVj Gddg Yfg (B: " (3QMeg Gddg (B. (3dbO CJYH ef HYOg (B" (3jQjO Gfg GdRege bOhI JJYH h dG JQjM h bGd ajg QShd Gddg Udi Gddg Ydjg h Sde (B:" (3CHhHcQ NjQ GdfGS GdG Gf jchf fHj s
Keywords: (3GdUOjb s; (3YHbQjI s